2018
DOI: 10.4168/aair.2018.10.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine to Treat Allergic Rhinitis: Evidence From a Meta-Analysis

Abstract: PurposeChinese herbal medicine (CHM) has been widely used in China to treat allergic rhinitis (AR). However, several studies have produced conflicting data with regard to the efficacy of the medicine. Our aim was to perform a meta-analysis of randomized clinical trials (RCTs) to evaluate the relative efficacy of CHM.MethodsWe systematically searched the PubMed, Medline, and Springer electronic databases up to March 2017 for RCTs comparing the efficacy of CHM versus placebo for the treatment of patients with AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
1
17
1
Order By: Relevance
“…559 More recently, a 2012 meta-analysis of 7 trials showed an improvement in symptom scores with traditional CHM, 558 but in a 2018 meta-analysis of 11 trials, there was improvement in QOL but not in symptom scores. 560 The 2012 National Health Interview Survey showed 34% of US adults used complementary health approaches, including herbal medicines, in the previous year. 561 Physicians need to question patients on their use of these products as they can have toxicity and drug-herb interactions.…”
Section: Herbal Medicationsmentioning
confidence: 99%
“…559 More recently, a 2012 meta-analysis of 7 trials showed an improvement in symptom scores with traditional CHM, 558 but in a 2018 meta-analysis of 11 trials, there was improvement in QOL but not in symptom scores. 560 The 2012 National Health Interview Survey showed 34% of US adults used complementary health approaches, including herbal medicines, in the previous year. 561 Physicians need to question patients on their use of these products as they can have toxicity and drug-herb interactions.…”
Section: Herbal Medicationsmentioning
confidence: 99%
“…There is an increasing demand for natural antioxidants for curing and prevention of diseases indicating that compounds in natural formulations are more active than their isolated form [31]. During the recent years many changes have occurred in the management of allergic rhinitis by using medicines in various traditional medicinal systems [32, 33]. A number of scientific investigations have proven the association between antioxidants and allergic diseases and antioxidant intake seems to have a protective effect on allergic diseases like rhinitis [3436].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Chinese Herbal Medicine (CHM) was found effective to reduce symptoms and enhance quality of life of patients with AR (Chan & Chien, 2014;Hon, Fung, Leung, Lam, & Lee, 2015;Lee et al, 2018;Zhang, Lan, Zhang, & Zhang, 2018). In the future, CHM may serve as an important supplementary means to AR treatment, although its specific biological mechanism remains to be further revealed.…”
Section: Arachidonic Acid Metabolismmentioning
confidence: 99%